2021
DOI: 10.3390/w13233374
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Yield and Reservoir Sedimentation in Highly Dynamic Watersheds: The Case of Koga Reservoir, Ethiopia

Abstract: Soil erosion is exacerbated by unsustainable land-use activities and poor management practices, undermining reservoir storage capacity. To this effect, appropriate estimation of sediment would help to adopt sustainable land-use activities and best management practices that lead to efficient reservoir operations. This paper aims to investigate the spatial variability of sediment yield, amount of sediment delivery into the reservoir, and reservoir sedimentation in the Koga Reservoir using the Soil and Water Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…Land degradation in Ethiopia has resulted from intentional soil erosion caused by land use and cover change due to overgrazing, urban expansion, deforestation, and growing agricultural business [7]. Tis soil erosion, in turn, exposed downstream watershed regions to high sediment yields and gradually raised the bed level of hydraulic schemes [8]. Furthermore, the sediment yield is the most serious issue in Ethiopia's subwatershed regions and ecosystems [9].…”
Section: Introductionmentioning
confidence: 99%
“…Land degradation in Ethiopia has resulted from intentional soil erosion caused by land use and cover change due to overgrazing, urban expansion, deforestation, and growing agricultural business [7]. Tis soil erosion, in turn, exposed downstream watershed regions to high sediment yields and gradually raised the bed level of hydraulic schemes [8]. Furthermore, the sediment yield is the most serious issue in Ethiopia's subwatershed regions and ecosystems [9].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that land is seen prograding towards the ocean is an indication that sediment is pilling in this region. The 8 Journal of Sensors vegetation and bare land have a favorable link because eroded soil contains fertile alluvial deposit, which encourages the growth of sparse and dense vegetation such as mangrove forest [33]. It should be noted that in this region, water is advancing into the land on a daily basis between noon and 6 p.m.…”
Section: Time Evolution Of Endmembersmentioning
confidence: 98%
“…Furthermore, catchment-scale studies in semi-arid (Haregeweyn et al, 2006;Girmay et al, 2012) and humid (Lemma et al, 2017;Moges et al, 2018;Kebedew et al, 2020;Lemma et al, 2020;Ayele et al, 2021) regions reported that water storage sites such as reservoirs and lakes have silted up owing to excessive runoff and associated sediment transport from various non-point sources in upland areas despite extensive implementation of various soil and water conservation (SWC) measures in croplands and non-croplands in the catchments (Haregeweyn et al, 2015). This can reflect that SWC measures have been implemented across watersheds without evaluating their effectiveness under specific land use and biophysical conditions.…”
Section: Introductionmentioning
confidence: 99%